NEW YORK TAX ADS - SHANNON,M (Tufts Archival Research Center, 2007)
Missing Attachments; Cover memo from Michael Shannon at Lorillard introducting New York tax ads. Asks for readers to review attached radio transcripts and latest print ad and to respond as soon as possible with approval.